Valorisation of Waste Oils Through Oleaginous Yarrowia lipolytica Yeast: Insights into Lipid Stability and Nutritive Properties of Lipid-Rich Biomass - Agata Urszula Fabiszewska; Joanna Kobus; Magdalena Górnicka; Aleksandra Piotrowicz; Iga Piasecka; Dorota Nowak (Applied Sciences)
This study investigated the potential of Yarrowia lipolytica, an oleaginous yeast, for producing lipid-rich biomass and its application in food technology. According to EFSA guidelines, lipid-rich biomass is recognized as a novel food with potential nutritional and technological value. However, cost-effective and scalable production of such biomass remains a challenge. The yeast was cultured in a nitrogen-limited medium using a cost-containment strategy based on the use of waste carbon sources, such as post-frying oil and untreated tap water. The composed batch culture approach studied in the experiments presented an example that reduces the cost of yeast biomass biosynthesis. This research aimed to characterize the biomass to assess its nutritional quality and suitability for food applications. Cultures were conducted in a laboratory bioreactor with a working volume of 4 litres. Key kinetic parameters were determined, including biomass yield (X), maximum lipid concentration (Lmax), lipid yield, protein yield relative to substrate and the specific rate of lipid synthesis or protein content and other cellular components. The biomass of Y. lipolytica demonstrated a high lipid content (39.43–50.53%), with significant levels of protein (24.16–27.03%) and unsaturated fatty acids, including oleic acid (62.73–66.44%) and linoleic acid (19.40–21.40%). Lipid-rich biomass produced in cultures with shorter times (20 h), which ended in the logarithmic growth phase, exhibited lower oxidative stability than longer cultures (65 h), which ended in the stationary growth phase. The results of this study highlighted that waste carbon sources and untreated tap water did not significantly impact the biomass yield or the nutritional profile, but did affect the stability of the produced oil. The biomass of Y. lipolytica, containing over 20% lipids, could serve as a promising raw material for food technology, providing a sustainable alternative to traditional vegetable oils. This work makes an important contribution to the development of alternative lipid sources by integrating waste processing in bioreactor-scale culture and kinetic modelling.